International experience of the e-government system development - Luzgina, Anastasiya N. (Journal of the Belarusian State University. Economics, 2018)
This paper reveals the essence of the concept of “e-government” and provides an overview of the main trends, spheres and areas of implementation of the public administration principles based on new technologies. The article briefly describes the situation in the sphere of e-government development. Most of the research work is devoted to studying the experience of the Visegrad Group countries (like Czech Republic and Hungary), as well as Georgia and Belarus. As part of the analysis this article highlights the main achievements, which the Czech Republic, Hungary and Georgia reached in the study area and identifies main problems (obstacles) for e-government development in the countries. The final part of the research work describes the e-government system creation in Belarus. Main tendencies as well as problems which describe the situation in the sphere are analysed in the paper. The work also provides recommendations to accelerate the implementation of e-government framework in the nearest future for Belarus.
Keywords: e-government; public administration; information and communication technology; electronic document management; electronic signature